Reflections on Covid-19 - Frederick, Marla Faye (Religion and society, 2020)
COVID-19, Religious Markets, and the Black Church, Marla Frederick Can You See the Big Picture? COVID-19 and Telescoping Truth, Yunus Doğan Telliel Learning from Religious Diasporas in Pandemic Times, Heather Mellquist Lehto